Purely positive or discriminatorily positive? The development of two-factor attitudes toward lesbians and gay men scales - Guo, Lingfeng; Fang, Shixin; Wen, Hongbo (Frontiers in Psychology, 2023)
Unidimensional bipolar scales based on prejudice against homosexuality neglect the effect of preference for heterosexuality on attitudes toward homosexuality. Additionally, the term “homosexuality” used in these scales may compromise their validity. The current study used person-centered and variable-centered approaches to examine the structure and classes of attitudes toward lesbians and gay men. In Study 1, we developed the Two-factor Attitudes toward Lesbians and Gay Men Scales, which have acceptable reliability and validity. The results obtained through variable-centered approaches suggest that a model comprising two factors (prejudice against homosexuality and preference for heterosexuality) was ideal. In Study 2, we explored the classes of attitudes toward lesbians and gay men through latent class analysis. The results supported a model containing three classes (purely positive, discriminatorily positive, and negative). This study validated a two-factor structure of attitudes toward lesbians and gay men, and it distinguished between purely positive and discriminatorily positive attitudes, thus providing an important reference for future research and interventions to promote public attitudes toward lesbians and gay men.